Feeding ecology and food preferences of Carcinoscorpius rotundicauda collected from the Pahang nesting grounds - John, Akbar; Yunus, Kamaruzzaman; Khan Chowdhury, Ahmed Jalal; Kassim, Zaleha (Penerbit UKM, 2012)
The first time report on the feeding ecology and food preference of mangrove horseshoe crab Carcinoscorpius rotundicauda (Latreille 1802) at their nesting grounds along the Pahang coast is given. Monthly sampling was carried out between March 2010 and February 2011 covering both monsoonal (March to October) and non-monsoonal (November to February) seasons. Major macrobenthic gut contents (bivalves, gastropods, crustaceans, polychaetes and miscellaneous food items including plant materials) were identified using microscopic examination. An electivity index (E1) was calculated for the frequent food items observed in the gut region of C. rotundicauda during monsoon and non-monsoon seasons. The EI was negative for crustaceans and positive for all the other food items including bivalves, gastropods, polychaetes and miscellaneous food items (which include insects, amphipods, Isopods, larval and juvenile stages of fishes, foraminifera and other Annelid worms). It is interesting to note that C. rotundicauda prefered less number of bivalves than polychaetes during non monsoon seasons but it was the reverse during monsoonal period. Male crabs intensely preyed on gastropods and female prefers polychaete worms during the peak mating/nesting season (June - August 2010). Seasonal variations in food composition showed that mollusks formed the main item especially gastropods. Unidentified organic matters in the gut content analysis of C. rotundicauda showed high preference towards plant materials. Gastro Somatic Index (GaSI) analysis showed that the feeding intensity of male crabs was higher during non-monsoon period while it was higher during monsoonal period in female crabs. In conclusion, the feeding ecology of mangrove horseshoe crabs were more similar to its closer and distant conspecifics. However, it was postulated that the higher preference of polychaete worms by the female C. rotundicauda during the peak mating season indicated its role in regulating the nesting behaviour